DESAIN DAN PENGUJIAN KINERJA KOMPOR GASIFIKASI-PIROLISIS - Johanis R Pangala; Armansyah H Tambunan; Hariadi Kartodihardjo; Gustan Pari (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2016)
This paper deals with the design and performance test of pyrolysis burning stoves that produce energy for cooking and biochar. The stove consists of two section chambers, namelycombustion chamber that produces activation heat for pyrolysis process and energy for cooking, andpyrolysis chamber that produces biochar and volatile matter (syngas and tar in gas form). Volatile matter product was introduced to the combustion chamber in addition to the biomass there and replaces biomass fuel gradually to produce energy for cooking and keeping the continuous pyrolysis process (autothermal). Methode used for performance test: direct observations/measurements and Water Boilling Test (WBT). Result of performance test: the autothermal process was going well until resulting a 100% biochar for most of the biomass used. Thermal efficiency of the stove was 11.3% (before pyrolysis) and 14.72% (after pyrolysis), excluding heat to produce biochar. Time needed to boil a 5 L water was 12 minutes before pyrolysis and 6 minutes after pyrolysis. Output power ranges from 9.60 kW to 23.16 kW. The maximum temperature reached 868 °C at the pan and 860oC in combustion chamber.Input biomass capacity depending on the type of feedstock ranging from 1200 - 3000 g/process, resulting in 507-900 g biochar/process, to give biochar ratio to raw materials from 23.0% to 44.8%. All maximum conditions occurs when volatilematters produced from pyrolysis process were burned, which showed that burning volatile matters is better than burning solid biomass directly.The amount of biochar produced by this stove was three times higher compared to anila stove, with less of smoke during the biochar production.